ANALISIS RISIKO BAHAYA KECELAKAAN KERJA DENGAN METODE HIAROC (HAZARD IDENTIFICATION, ASSESMENT OF RISK & OPPORTUNITIES & CONTROL): Studi Kasus: PT Dekor Asia Jayakarya - Putra, Bimo Haykal Nugroho; Yuamita, Ferida (Yayasan Education and Social Center, 2024)
The Work Safety Act Number 1 of 1970 regulates the protection of workers' safety during their duties, aiming to enhance their well-being and productivity. To control health and safety hazards effectively, occupational health and safety management is crucial in reducing workplace accidents. PT Dekor Asia Jayakarya, a company in the crafts industry, continues to experience accidents ranging from low to high risks. Between February and April 2023 alone, there were two recorded incidents. Given these challenges, a study will be conducted to identify potential hazards in the production processes at PT Dekor Asia Jayakarya's Warehouse area. The objective is to understand the potential risks associated with production activities in that area and determine preventive measures to mitigate these risks. Job Safety Analysis (JSA) and Safe Working Procedures (SWP) methods will be employed to meticulously analyze each task within the Warehouse production processes. This approach aims to identify potential hazards and establish safe work procedures to reduce risks in the workplace. The primary focus of this research is to ensure that every step in the Warehouse production processes is conducted with safety considerations in mind, thereby fostering a safer work environment and supporting sustainable productivity